BUDAYA LITERASI DALAM MENINGKATKAN KREATIVITAS BELAJAR SISWA DI SMP ZAINUDDIN WARU SIDOARJO - Rosyidah, Ainur; Musawir (STAI Pelabuhan Ratu, 2024)
Education is a process of passing on cultural values ​​from one generation to the next generation through the learning process. Education and literacy are two very important things. The aim of this research is to describe and analyze literacy culture in increasing student learning creativity at Zainuddin Waru Middle School, Sidoarjo. This research uses a qualitative method with a phenomological approach. As primary data, the data source comes from selected informants, including school principals, curriculum staff, teachers and students. As secondary data in the form of relevant books and journals. Data collection techniques in this research were interviews, observation and documentation. This research uses data analysis by reducing data, presenting data and drawing conclusions or verification. The results of the research show that the culture of literacy in increasing students' learning creativity has gone well. This can be implemented by students carrying out literacy activities in the morning known as